Pengaruh intensitas penggunaan platform artificial intelligence terhadap motivasi belajar mahasiswa - Nurul Atiba; Edy Herianto; Basariah Basariah (Journal of Education, Cultural and Politics, 2026)
This study aims to investigate the influence of the intensity of using Artificial Intelligence (AI) platforms on the learning motivation of students in the Pancasila and Citizenship Education (PPKn) Study Program at the University of Mataram. Along with the rapid digital transformation in higher education, AI has become a cognitive support instrument that affects the psychological dynamics of students in learning. This study used a quantitative approach with the ex post facto method. The research population consisted of PPKn students from the class of 2022, with a sample size of 66 respondents determined through stratified proportional random sampling technique. Data were collected using a Likert scale questionnaire that had been tested for validity and reliability (Cronbach's Alpha for variable X = 0.896 and Y = 0.996). Data analysis techniques included simple linear regression and One-Way ANOVA. The results showed that the intensity of AI use had a positive and significant effect on student learning motivation (Sig. 0.000 < 0.05) with a regression coefficient of 0.296. The results of the One-Way ANOVA also showed significant differences in learning motivation between intensity groups (F = 5.603; Sig = 0.006). Post Hoc Tukey further testing revealed that a significant surge in motivation occurred when students moved from low to moderate use levels, but tended to stabilize from moderate to high levels. This study concludes that AI acts as a motivational catalyst through the ease of access to information and the enhancement of students' academic confidence in mastering complex materials.